Molecular evidence of hepatozoonosis in tigers of Vidarbha region of Maharashtra State of India - S. M. Kolangath; M. D. Pawshe; S. V. Upadhye; V. M. Dhoot; M. S. Patil; R. M. Kolangath (BMC Veterinary Research, 2024)
Abstract Background Hepatozoonosis has been reported in many species around the world. Few incidences have been reported in various species of wild felids. Tigers are endangered large cats and are protected under the Wildlife Protection Act, 1972 under Schedule I. The study was carried out to estimate the positivity rate of hepatozoonosis in tigers of the Vidarbha region of Maharashtra, India. Methods Blood (n = 21) or tissue samples (n = 5) were collected from 26 wild captured / zoo-born or dead tigers during the quarantine period/post-mortem examination. Blood smear examination along with Polymerase Chain Reaction (PCR) studies were conducted for the detection of hepatozoonosis. All the amplicons from the positive samples were purified and sequenced, and the sequences were subjected to nBLAST analysis to detect the species of Hepatozoon. The sequences were deposited into public domain database of National Center for Biotechnology Information (NCBI) and accession numbers were allotted. A phylogenetic study was undertaken to understand the evolutionary lineage of the pathogen. Tissue distribution studies were carried out on tissue samples received during post mortem. A clinical case in a tiger cub was managed and sub-clinical cases were monitored for relapse. Age-wise, sex-wise, region-wise and captive time-wise positivity rate was estimated. The data was analyzed using statistical tools. Results A total of 12 tigers were found positive for H. felis during the screening. A clinical case was diagnosed and successfully treated. The age group of 0–3 years reported a positivity rate of 66.66%, and all the cases found positive were reported between the age group of 0–7 years. Males reported a positivity rate of 58.33 per cent, while females reported 35.71%. Taboba and Andhari Tiger Reserve of the state had a positivity rate of 52.94 per cent. However, the statistical analysis for blood parameters and positivity rate by ‘t’ test and Chi-squared test were found to be non-significant. Conclusions An overall positivity rate of 46.15% indicates the wide distribution of hepatozoonosis among wild tigers of the Vidarbha region of Maharashtra, India, which is strategically important considering the gene flow and migration of tigers. Hepatozoonosis can progress to clinical outcomes in young animals and require veterinary intervention. Molecular tools and phylogenetic studies can supplement important data on circulating species of Hepatozoon in the field. Further studies on the clinical management and epidemiology of the infection in wild felids will comprehend the cause of wildlife conservation.